2006
DOI: 10.1029/2005jd006428
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ice storms and management practices on current carbon sequestration in forests with potential mitigation under future CO2 atmosphere

Abstract: [1] Ice storms are disturbance events with potential impacts on carbon sequestration. Common forest management practices, such as fertilization and thinning, can change wood and stand properties and thus may change vulnerability to ice storm damage. At the same time, increasing atmospheric CO 2 levels may also influence ice storm vulnerability. Here we show that a nonintensively managed pine plantation experienced a $250 g C m À2reduction in living biomass during a single storm, equivalent to $30% of the annua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 53 publications
2
62
2
Order By: Relevance
“…Our results also show that At the stand or regional level, NEE is significantly affected by disturbances (Law et al, 2004). Disturbances can substantially alter ecosystem carbon fluxes and regional carbon budgets (McCarthy et al, 2006;Chambers et al, 2007), by reducing the aboveground biomass and increase litter, thereby leading to a decrease in GPP and an increase in R h . Our results show that disturbances including wildfires and hurricanes could affect regional annual NEE.…”
Section: Year-to-year Variationssupporting
confidence: 48%
“…Our results also show that At the stand or regional level, NEE is significantly affected by disturbances (Law et al, 2004). Disturbances can substantially alter ecosystem carbon fluxes and regional carbon budgets (McCarthy et al, 2006;Chambers et al, 2007), by reducing the aboveground biomass and increase litter, thereby leading to a decrease in GPP and an increase in R h . Our results show that disturbances including wildfires and hurricanes could affect regional annual NEE.…”
Section: Year-to-year Variationssupporting
confidence: 48%
“…1). This variation can be attributed to a number of causes: variations in water availability, the occurrence of a severe ice storm in December 2002 resulting in canopy damage and changes in sink dynamics (31), and changes in L D as the stand progressed to a closed canopy state ( When NPP and L D data were pooled across the four FACE sites [supporting information (SI) Table 1], after excluding the data from drought years and before canopy closure at Duke FACE, NPP was linearly related to L D ( Fig. 3A; n ϭ 40, P Ͻ 0.001 for both current and elevated [CO 2 ]; regression analysis was performed on single treatment-year data points, but we show treatment means and standard errors of each site) and significantly higher under elevated [CO 2 ] (P ϭ 0.039).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been reported that slight topographical relief at the experimental site in Duke Forest generated a "treatment-similar" effect on plant productivity and C input to the soil (51,53,62), thus further disturbing the effects of CO 2 and N treatments. In addition, recent weather events contributed to increased spatial heterogeneity through uneven impact across the site (54). The resulting high heterogeneity of soil chemical properties makes it difficult to isolate the signal of the effect of elevated CO 2 or N amendment on soil bacterial diversity and community structure.…”
Section: Discussionmentioning
confidence: 99%